ACCOUNTING AND THE LAW. - Berle, A. A. (The Accounting Review, 1938)
The article attempts to stimulate a more systematic method of evolving standard, but evolutionary, rules of accounting. The conclusion follows from two premises. First, rules of accounting have become, in large measure rules of law. Second, that the present methods by which accounting theory is translated into the accounting rules or, if one chooses, into accounting practices, which thus enter the legal system, are not wholly satisfactory, especially in view of the results which now follow from that translation. By consequence, the task of developing a systematic yet flexible means of arriving at and recording the sound doctrine as it appears in the light of the knowledge of the day, takes the foreground as a major problem in the profession of accounting. Economist John Bauer, indicated that accounting development had paralleled, roughly, the enormous growth of business over the past half-century; and he concluded by insisting, also accurately, that the growing control of government over business furnished a powerful spur toward extending the best private practice to all business units in similar fields.